Optimizing mirid control on cocoa farms through complementary monitoring systems. (20th May 2016) - Awudzi, G. K.; Cudjoe, A. R.; Hadley, P.; Hatcher, P. E.; Daymond, A. J.
Abstract: Mirids ( Sahlbergella singularis and Distantiella theobroma ) are the most important insect pests affecting cocoa production across West Africa. Understanding the population dynamics of mirids is key to their management; however, the current recommended hand‐height assessment method is labour intensive. The objective of the study was to compare recently developed mirid sex pheromone trapping and visual hand‐height assessment methods as monitoring tools on cocoa farms and to consider implications for a decision support system. Ten farms from the Eastern and Ashanti regions of Ghana were used for the study. Mirid numbers and damage were assessed fortnightly on twenty trees per farm, using both methods, from January 2012 to April 2013. The mirid population increased rapidly in June, reached a peak in September and began to decline in October. There was a significant linear relationship between numbers of mirids sampled to hand‐height and mirid damage. High numbers of male mirids were recorded in pheromone traps between January and April 2012 after which there was a gradual decline. There was a significant inverse relationship between numbers of trapped adult mirids and mirids sampled to hand‐height (predominantly nymphs). Higher temperatures and lower relative humidities in the first half of the year were associated with fewer mirids at hand‐height, but larger numbers of adult males were caught in pheromone traps. The study showed that relying solely on one method is not sufficient to provide accurate information on mirid population dynamics and a combination of the two methods is necessary.